GLOBAL WARMING AND ITS IMPACT ON MANGROVE LAND DEGRADATION ON THE NORTH COAST OF BENGKALIS ISLAND, RIAU PROVINCE - Maulana, Luxni; Syamsunasir, Syamsunasir; Suwarno, Panji; Aris, Tomi (Journal of Agriculture, 2022)
Bengkalis Regency is located on the north coast of Riau Province, where the coastal area is very vulnerable to the threat of maritime disasters. Global warming can result in natural disasters, which means catastrophe on earth. Global warming causes an increase in the temperature of the earth's surface. This study aims to analyze the progress of the coastline and sea level rise that occurs and their impact on the degradation of Mangrove land on the north coast of Bengkalis Island, Riau Province. The research method used is the quantitative method through analysis of satellite images to map predictions of abrasion in the future. Data processing is carried out using satellite image data with different temporal, namely 1991, 2002, 2012, and 2021. Analysis of shoreline change predictions is carried out using the Digital Shorelines Analysis System Method. Utilization of GIS data can be used to map areas with the potential for abrasion, and make anticipatory measures against abrasion that may occur. In Bengkalis Regency itself, several efforts have been made by the local government, namely through mangrove planting programs, and increasing public awareness.